Delivery of mental health treatment to combat veterans with psychiatric diagnoses and TBI histories. - Shannon R Miles; Juliette M Harik; Natalie E Hundt; Joseph Mignogna; Nicholas J Pastorek; Karin E Thompson; Jessica S Freshour; Hong J Yu; Jeffrey A Cully (PLoS ONE)
Traumatic brain injury (TBI) and mental health (MH) disorders are prevalent in combat veterans returning from Afghanistan and/or Iraq (hereafter referred to as returning veterans). Accurate estimates of service utilization for veterans with and without TBI exposure (referred to as TBI history) are imperative in order to provide high quality healthcare to returning veterans. We examined associations between TBI history and MH service utilization in a subsample of returning veterans who were newly diagnosed with posttraumatic stress disorder (PTSD), depression, and/or anxiety in the 2010 fiscal year (N = 55,458). Data were extracted from the Veterans Health Administration (VHA) National Patient Care Database. Veterans with MH diagnoses and TBI histories attended significantly more psychotherapy visits, (M = 8.32 visits, SD = 17.15) and were more likely to attend at least 8 psychotherapy visits, (15.7%) than veterans with MH diagnoses but no TBI history (M = 6.48 visits, SD = 12.12; 10.1% attended at least 8 sessions). PTSD and TBI history, but not depression or anxiety, were associated with a greater number of psychotherapy visits when controlling for demographic and clinical variables. PTSD, anxiety, depression, and TBI history were associated with number of psychotropic medication-management visits. TBI history was related to greater MH service utilization, independent of MH diagnoses. Future research should examine what MH services are being utilized and if these services are helping veterans recover from their disorders.